Magnetic and hydrophobic sorbent based on glauconite for the removal of oil slick from the water surface - Belousov P. E. Petr Evgenjevich; Gorbunova E. M. Elena Mikhaylovna; Kim K. B. Kseniya Borisovna; Niftaliev S. I. Sabukhi Ilich-ogly; Krupskaya V. V. Viktoriya Valerjevna; Rudmin M. A. Maksim Andreevich; Koroleva T. A. Tatjyana Aleksandrovna; Rumyantseva A. O. Anastasiya Olegovna (2025, 2025)
Title screen.